Analyzing the differences between reads and contigs when performing a taxonomic assignment comparison in metagenomics - Rodríguez-Brazzarola, Pablo; Perez-Wohlfeil, Esteban; Díaz-del-Pino, Sergio; Holthausen, Ricardo; Trelles-Salazar, Oswaldo Rogelio (Springer, Cham, 2018)
Metagenomics is an inherently complex field in which one of the primary goals is to determine the compositional organisms present in an environmental sample. Thereby, diverse tools have been developed that are based on the similarity search results obtained from comparing a set of sequences against a database. However, to achieve this goal there still are affairs to solve such as dealing with genomic variants and detecting repeated sequences that could belong to different species in a mixture of uneven and unknown representation of organisms in a sample. Hence, the question of whether analyzing a sample with reads provides further understanding of the metagenome than with contigs arises. The assembly yields larger genomic fragments but bears the risk of producing chimeric contigs. On the other hand, reads are shorter and therefore their statistical significance is harder to asses, but there is a larger number of them. Consequently, we have developed a workflow to assess and compare the quality of each of these alternatives. Synthetic read datasets beloging to previously identified organisms are generated in order to validate the results. Afterwards, we assemble these into a set of contigs and perform a taxonomic analysis on both datasets. The tools we have developed demonstrate that analyzing with reads provide a more trustworthy representation of the species in a sample than contigs especially in cases that present a high genomic variability.
Keywords: Bioinformática - Congresos; Taxonomic assignment; Sequencing analysis; Metagenomic comparison